PANDANGAN UMAT KATOLIK TENTANG MARIA BUNDA ALLAH - Intan Martina; Don Bosco Karnan Ardijanto (Bahasa Indonesia, 2021)
The Catholic Church believes in and teachs that Mary is the Mother of God. However, the teaching on Mary, the Mother of God until now has caused either agree or disagree among the people of God. Based on this fact, there are some questions, namely: How is the teaching of the Church on Mary, the Mother of God? How is the perception of Basic Ecclesial Community on Mary, the Mother of God. This study aimed to explore and elaborate on the teaching of the Church on Mary, the Mother of God and to describe the perception of the Saint Gilles Asisi Basic Ecclesial Community of Mater Dei Parish, Madiun on Mary, the Mother of God. Therefore, to achieve these objectives, this study used qualitative method. The selection of respondents used purposive sampling technique, while data collection was done through interviews.This study produced two conclusions. First, the Chtholic Church believe in and teaches that Mary is the Mother of God. The teaching is based on the Scripture and states in Lumen Gentium, Redemptoris Mater, Mulieris Dignitatem, and the Catechism of the Catholic Church. Second, the Basic Ecclesial Community believe that Mary, the Mother of God. They venerate Mary,the Mother of God in some ways: celebrating the liturgical celebration of Mary and devotional practices.